Autoantibodies against phosphatidylserine-prothrombin complex in patients with systemic sclerosis. Issue 11 (12th October 2004) - Hasegawa, M; Sato, S; Yanaba, K; Komura, K; Yamazaki, M; Takehara, K
Abstract : Objective: To determine the frequency and clinical association of antiphosphatidylserine-prothrombin complex (PS/PT) antibody (Ab) in systemic sclerosis (SSc). Methods: Anti-PS/PT IgG Ab was examined by enzyme linked immunosorbent assay (ELISA) in 112 patients with SSc. Thirty three healthy volunteers and 30 patients with systemic lupus erythematosus (SLE) were also investigated as controls. Results: Anti-PS/PT Ab was detected in 18/112 (16%) patients with SSc and 10/30 (33%) patients with SLE, whereas it was not detected in any normal controls. Anti-PS/PT Ab was more frequently detected in patients with SSc with peripheral ischaemia and lung disease (pulmonary fibrosis and pulmonary hypertension) than in patients with SSc without the Ab. However, anti-PS/PT Ab was not associated with the severity of skin sclerosis. Importantly, two patients were negative for both lupus anticoagulant and Ab against cardiolipin β2 -glycoprotein I complex among six anti-PS/PT Ab positive patients with SSc and a thromboembolic episode. Conclusions: Anti-PS/PT Ab is associated with thromboembolism, peripheral ischaemia, and lung involvement in some patients with SSc. Examination of this Ab may be useful to recognise the risk of thromboembolism in patients with SSc.